JOURNAL OF GOVERNMENT & POLITICS : Facial Morphometrics, Voters' Facial Preferences, and Electoral Outcomes - Jamairah A. Nagamora, Elika ER C. Bienes (FISIPOL UMY, 2016)
Elections operate in such manner that voters must have researched well the political backgrounds and platforms of the candidates they are voting.